A developmental origins perspective on the emergence of violent behavior in males with prenatal substance exposure. Issue 1 (21st December 2018) - Terrell, Sarah; Conradt, Elisabeth; Dansereau, Lynne; Lagasse, Linda; Lester, Barry
ABSTRACT: Children with prenatal substance exposure are at increased risk for externalizing behavior problems and violence. However, the contribution of early life experiences for placing these individuals at risk is not well understood. Utilizing a sample of 1, 388 children with prenatal substance exposure from the Maternal Lifestyle Study, we attempt to shed light on these contributing factors by examining the impact of infant temperament, maternal sensitivity, and early life stress on the expression of violent behavior at ages 12 through 14 years. Males may be more at risk for increases in violent behavior in early adolescence through a number of early life experiences, such as variability in responses to maternal flexibility and engagement related to individual differences in temperament, as well as exposure to early adversity. Comparing two prevailing developmental theoretical frameworks, deficit models and differential susceptibility, we aim to understand the developmental origins of violent behavior in males by identifying children who may be most susceptible to early caregiving experiences.